Fatwa MUI Tentang Riba:“Dampak dan Relevansinya di Era Ekonomi Digital” - Rifqi; Dzaky , Muhammad; Farhan , Muhammad; Az-Zahra , Casilda Aliya; Fauzan, Muhammad (Tabayyun : Journal Of Islamic Studies, 2024)
Usury is a part of buying and selling that has been prohibited by Allah since the time of the Prophet Muhammad SAW, usury has existed since the era of ignorance, economically it has been used by capital owners to exploit poor people in order to obtain as large and as large a profit as possible. The digital era influences various usurious transactions in the digital economy. The existence of massive technological developments has resulted in a significant impact of usury in the economy, especially in the current digital era. In this regard, all ulama agree that usury which is practiced in the current digital era is prohibited because there is an element of exploitation which causes injustice from the owner of the capital to the borrower, therefore the majority of ulama usury is a source of haraam. In Indonesia, usury has been explained in MUI fatwa number 1 of 2004 concerning bank interest issued to promote or increase the prestige of sharia banks so that people switch to sharia banks and leave conventional banks. A usurious economic system can create continuous disparities in economic growth in the world community. This research found that usury is no longer relevant in this digital era, there needs to be a re-discussion so that the fatwa is appropriate to the existing situation. It is hoped that this research will be able to contribute ideas to add scientific references and considerations in future research.